CRITICAL REVIEW OF DRUG PROMOTIONAL LITERATURE USING THE WORLD HEALTH ORGANISATION GUIDELINES (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: Drug promotional literature (DPLs) is used to promote new drugs entering the market to doctors. The objective of the present study is to evaluate the accuracy of DPLs by using the World Health Organisation (WHO) criteria. Methods: An observational study was conducted from August 2024 to January 2025 at B.S. Kushwaha Institute of Medical Sciences, Kanpur. The DPLs were collected from various hospital outpatient departments. The literature was evaluated according to the criteria set by the WHO. Result: Three hundred DPLs were evaluated. Cardiovascular drugs (51 [17%]) were most frequently promoted, followed by antidiabetic drugs (46 [15.3%]) and antimicrobial agents (44 [14.7%]). A single drug was promoted in 201 (67%) and a fixed-dose combination in 99 (33%) brochures. Manufacturer’s name was mentioned in 291 (97%), but their address was mentioned in 165 (55%) claims only. Drug cost was revealed only in 30 (10%) DPLs. Each ingredient’s generic name, brand name, and dosage form were mentioned in 294 (98%) brochures. Indication for use was stated in 290 (96.7%) claims. Contraindications, adverse effects, precautions, and drug interactions were listed in 103 (34.3%), 98 (32.7%), 98 (32.7%), and 88 (29.3%) advertisements, respectively. References were cited in 200 (66.7%) brochures. Only 95 (31.7%) literatures had relevant pictures of drugs being promoted and 89 (29.7%) had a graphical representation of pharmacological properties. A total of 207 (69%) DPLs followed more than 50% of the WHO criteria. Conclusion: Majority of DPLs satisfied only half of the WHO criteria for rational drug promotion, and none of them fulfilled all the specified criteria. Incomplete or exaggerated information in DPLs may mislead and result in irrational prescriptions.